Long‐Lived Excited‐State Dynamics of i‐Motif Structures Probed by Time‐Resolved Infrared Spectroscopy. Issue 9 (17th February 2016) - Keane, Páraic M.; Baptista, Frederico R.; Gurung, Sarah P.; Devereux, Stephen J.; Sazanovich, Igor V.; Towrie, Michael; Brazier, John A.; Cardin, Christine J.; Kelly, John M.; Quinn, Susan J.
Abstract: UV‐generated excited states of cytosine (C) nucleobases are precursors to mutagenic photoproduct formation. The i‐motif formed from C‐rich sequences is known to exhibit high yields of long‐lived excited states following UV absorption. Here the excited states of several i‐motif structures have been characterized following 267 nm laser excitation using time‐resolved infrared spectroscopy (TRIR). All structures possess a long‐lived excited state of ∼300 ps and notably in some cases decays greater than 1 ns are observed. These unusually long‐lived lifetimes are attributed to the interdigitated DNA structure which prevents direct base stacking overlap. Abstract : Exciting longevity : UV excitation of the four‐stranded cytosine i‐motif produces excited states lasting into the nanosecond region, suggesting that they are vulnerable to photodamage. A variety of i‐motif forming structures are probed using time‐resolved infrared spectroscopy. Distinctive transient IR features are observed and their possible origins discussed with reference to the unique structure of the i‐motif.